Sistem Informasi Inventory Aset dan Logistik Rumah Sakit Bina Kasih Berbasis Website dengan Menggunakan Metode Rapid Application Development (RAD) - Limbong, Tonni; Sianipar, Julyannes Ferdinand (UNIKA Santo Thomas, 2022)
Bina Kasih Hospital is a health institution that does not yet have an information system for asset inventory and logistics. In the development of increasingly advanced technology requires agencies to provide information quickly and accurately. The website-based Bina Kasih Hospital Asset Inventory and Logistics Information System will later be used to support the productivity of the logistics department in carrying out the procurement process, recording and managing asset inventory and logistics reports. The method in developing the Asset Inventory and Logistics Information System uses the rapid application development (RAD) method in the process and the author tests the system using blackbox testing